FAKTOR KUALITAS KEHIDUPAN KERJA DAN KETERLIBATAN KARYAWAN - Rusdin Rusdin (Universitas Bunda Mulia, 2017)
Efforts to realize the performance of SOEs is a very urgent requirement. This is related to the state ministry in Indonesia stakeholder‟s strategic plan 2012-2014. One important element in achieving this is improving the Quality Planning, Human Resources and Financial Management that can act as a surveillance tool as well as performance drivers. Therefore, through this study has explored: (1) the quality of work life, such as career plane, (2) organizational citizenship behavior, such as work ethic issues, and (3) employee engagement, such as remuneration policy issues. The research was conducted by applying a survey of 429 people Associate Manager at 141 state-owned enterprises in Indonesia. Data was collected by indirect communication techniques through instruments such as questionnaires and interview techniques through limited direct communication and documentation study. The study was conducted from January 2011, which ended December 31, 2012. The data processing techniques with descriptive analysis, the weighted mean score and inferential analysis of the Structural Equation Modeling (SEM). The results showed that: (1) Quality of work life, organizational citizenship behavior, employee engagement in SOEs in Indonesia showed a good condition, but not optimal, (2) quality of working life and organizational citizenship behaviors have a positive and significant effect on state employee engagement in Indonesia. The implications of this research, requiring hard work of the managers at levels 1 and 2 under the above directors and executive managers, to accommodate the interests of the manager as agent, and as the principal stakeholder‟s interests. Requires wisdom and policy decisions to implement the system of participation button up and participation from the top down. Keywords: quality of work life, employee engagement